2009
DOI: 10.1021/jp808931k
|View full text |Cite
|
Sign up to set email alerts
|

Delocalization of 4f Electrons in Gadolinium Oxide on the Nanometer Scale

Abstract: Some metals such as silver are known to become strong reducers on the nanometer scale. Electron energyloss spectroscopy (EELS) shows that modifications of the electronic structure of metal ions also arise in nanoparticles of gadolinium oxide. Indeed, the oxygen K and gadolinium N 4,5 edges present modifications for particles size below 1.5 nm which are the signature of an hybridization of the initially atomiclike Gd 4f states with the valence band and especially the O p states. These modifications evidence tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…We are in an experimental situation where the collection aperture For instance, let us now consider a cluster with 86 atoms which contains the probed oxygen at its centre. This cluster is very similar to the NP experimentally studied in a previous paper [8]. Figure 4 shows the six intrinsic components used in the case of c trichroism (see section 2.3).…”
Section: Elnes Signal For a Probed Oxygen Sitesupporting
confidence: 77%
See 2 more Smart Citations
“…We are in an experimental situation where the collection aperture For instance, let us now consider a cluster with 86 atoms which contains the probed oxygen at its centre. This cluster is very similar to the NP experimentally studied in a previous paper [8]. Figure 4 shows the six intrinsic components used in the case of c trichroism (see section 2.3).…”
Section: Elnes Signal For a Probed Oxygen Sitesupporting
confidence: 77%
“…In the present paper, we have used Gd 2 O 3 NPs, wellcalibrated in size, which were recently studied by EELS [8].…”
Section: Gd 2 O 3 Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the radial extension of the 4f orbitals is small, increases in 4f orbital covalency have primarily been achieved by minimizing the energy separation (degeneracy driven covalency). 127,138,139 Within the limits of this model, changes in the intensity of the O K-edge can be rationalized using eqn (1) in the following manner: Fig. 9 shows how the spectra can be partitioned into several groups with distinct behavior, and correlates well with expectations from the physical and theoretical studies described above.…”
Section: Systematic Trends In Ln-o Bondingsupporting
confidence: 56%
“…Such a charge-transfer scenario, implying certain covalency for Gd 3+ 4 f states, would be in line with our RIXS findings. The more delocalized Gd 3+ 4 f states may also play a role in the enhanced relaxitivities in the EMFs, as recent studies on Gd 2 O 3 nanoparticles showed enhanced relaxitivities when particle size approaches to 3 nm that Gd 4 f wave functions become comparable to the particle size 32 , 33 .…”
Section: Discussionmentioning
confidence: 99%